1995
DOI: 10.1016/s0335-7457(05)80335-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration and testosterone on Fel d I production by sebaceous glands of male cats: II—morphometric assessment

Abstract: A morphometric study of cat sebaceous glands was performed to evaluate the effects of castration and testosterone treatments. Skin biopsies were taken in six cats before castration, after castration and after the testosterone injections administered after castration (total number of biopsies: 18). Ninety 811m thick sections of each biopsy were assessed for image analysis processing (SAM BA 2005, ALCATEL TITN). The variations in glands and cells size were evaluated on digitized microscopic images by morphometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Production of Eel J I by skin and by sebaceous glands in the latter was confirmed by studies done by our group [5,6]. Furthermore, it was recently demonstrated that Eel d I concentrations on the skin are under hormonal control in parallel with the sebaceous cells and glands volume [7]. Cats have tubular anal glands which have been described in histochemical study as structures of apocrine and holocrine glands with a large amount of sebaceous glands and secretion of sebum, proteins, and lipids [10].…”
Section: Introductionmentioning
confidence: 59%
“…Production of Eel J I by skin and by sebaceous glands in the latter was confirmed by studies done by our group [5,6]. Furthermore, it was recently demonstrated that Eel d I concentrations on the skin are under hormonal control in parallel with the sebaceous cells and glands volume [7]. Cats have tubular anal glands which have been described in histochemical study as structures of apocrine and holocrine glands with a large amount of sebaceous glands and secretion of sebum, proteins, and lipids [10].…”
Section: Introductionmentioning
confidence: 59%
“…Fel d 1, the major cat allergen, is an uteroglobin expressed in salivary glands and skin. The production of Fel d 1 is related to sexual hormones . Three allergens are known to have surfactant properties, Equ c 1, Equ c 4, and Fel d 8.…”
Section: Major and Relevant Minor Allergenic Moleculesmentioning
confidence: 99%
“…[25][26][27][28][29] Male cats exhibit higher levels of the protein and, on castration, reach similar levels compared with female cats. 30 Although some function in pheromone binding 31 and pelt conditioning has been suggested, the biological function of Fel d 1 remains uncertain. A vaccine targeting Fel d 1 in cats will affect the allergic response at the first possible point of intervention by inducing Fel d 1-specific antibodies in the animal.…”
Section: Abbreviations Usedmentioning
confidence: 99%